Efektivitas Penegakan Hukum Lingkungan Hidup terhadap Aktivitas Manusia Penyebab Banjir: Studi Kasus di Aceh Tamiang - Rayi Kharisma Rajib; Ayuk Pebriyani; Amanda Dwi Yunita (INDO PUBLISHING, 2026)
Flooding is a classic problem that continues to recur in various regions in Indonesia, including in Aceh Tamiang Regency. This phenomenon is not only seen as an impact of high rainfall or the geographical position of the region but also seen as a consequence of ecosystem damage due to human intervention that ignores environmental sustainability. This study aims to identify the factors that trigger flooding in Aceh Tamiang and analyze the effectiveness of environmental law enforcement in flood mitigation efforts. A normative juridical method with a descriptive nature is used in this study, the implementation of which relies on library studies of primary, secondary, and tertiary legal materials. The results of this study provide an overview of flooding in Aceh Tamiang influenced by high rainfall, river sedimentation, land conversion, illegal logging, sand mining, residential development on riverbanks, and minimal public awareness in environmental conservation. Environmental law enforcement is actually regulated in Law Number 32 of 2009 through preventive and repressive efforts but the reality of implementation in the field has not been optimal due to weak supervision, lack of firm sanctions, and low public awareness. Therefore, the effectiveness of flood management depends heavily on the firmness of legal instruments supported by integration between the government, law enforcement, and community elements in safeguarding environmental protection.